Pengembangan Google Sites Sebagai Media Pembelajaran Mandiri pada Mata Pelajaran Bahasa Inggris Kelas IX di SMP - Risa Winanti; Abna Hidayati; Fitri Yeni Juwita; Novrianti (Lembaga Intelektual Muda (LIM) Maluku, 2026)
The limitations of digital-based independent learning media for Report Text material indicate the need to develop media that support the achievement of English competencies according to the Independent Curriculum, especially the Learning Outcomes (CP) of Literacy-Independence and CP of Understanding Implicit Information. This study aims to develop and test the validity and practicality of Google Sites as an independent English learning media for ninth-grade students. This study uses the Research and Development (R&D) method with a 4D model that includes the Define, Design, Develop, and Disseminate stages. The product was validated by media experts and material experts, then its practicality was tested by one English teacher and 25 ninth-grade students of SMP Negeri 2 Kubung. Data were collected using a 1–5 Likert-scale questionnaire and analyzed based on the average value. The results showed that the media expert validation obtained an average of 4.52 and the material expert 4.85, which indicates that the product is very valid and feasible to use. The practicality test obtained a combined average of 4.69, indicating that Google Sites is very practical, easy to use, and supports independent learning. This research only reached the validity and practicality testing stage, so the product's effectiveness has not been tested. Therefore, the developed Google Sites is declared valid and practical as a medium for independent English learning for Report Text material.